Abolitionism and the Paradox of Penal Reform in Australia: Indigenous Women, Colonial Patriarchy, and Co-option - Baldry, Eileen (Social justice, 2014)
The article discusses prison abolitionism and penal reform in Australia, focusing on the experience of Indigenous women. Topics include Australia's colonial history; prison and judicial discrimination on the basis of race, class, sexuality, age and ability; and the criminalization of Indigenous peoples within the post-colonial context.